I'm not cute! - Allen, Jonathan (Boxer Books UK, 2010)
*I'm Not Cute!* is a humorous and heartwarming story about a little panda named Poppy who insists she$1 (Bs not cute, despite everyone around her thinking otherwise. As Poppy encounters different situations, she tries to prove her toughness, but ultimately learns that being cute isn$1 (Bt such a bad thing after all. The book celebrates self-expression and the playful charm of accepting who you are.s